Att studera askmoln med GNSS - Nguyen, Björnborg; Sjöberg, Mattias (My University, 2014)
Abstract In this report the technique of observing volcanic ash in the atmosphere by analyzing SNR data (Signal-to-Noise Ratio) from GNSS (Global Navigation Satellite System) stations was investigated. The functionality of the method was confirmed by studying volcanic plumes from three areas: Iceland, Sicily and Indonesia. A number of programs were written for data analysis. The timing and direction of the observed detections for Eyjafjallaj¨okull (2010) and Etna (2006) proved to fit with data from other detection techniques. During early 2014 several volcanoes (i.a. Sinabung, Kelut and Merapi) in Indonesia were erupting relatively simultaneously. A large number of volcanic plumes could therefore be detected there. By combining data from several satellites and receivers information about the location of the volcanic ash plumes could be obtained. The advantages of this technique include its relatively low costs and its potential for continuous and comprehensive observation opportunities. In the future there are good opportunities for SNR data analysis from GNSS stations to function as a complement to current detection techniques.
Keywords: Energi; Geovetenskap och miljövetenskap; Klimatforskning; Energy; Earth and Related Environmental Sciences; Climate Research